Catalytic and Thermal Decarboxylation of Mg-Zn Basic Soap to Produce Drop-in Fuel in Diesel Boiling Ranges - Neonufa, Godlief F.; Soerawidjaja, Tatang H.; Prakoso, Tirto (ITB Journal Publisher, LPPM ITB, 2017)
Fatty acid deoxygenation is a method for producing renewable hydrocarbon fuels such as green diesel, jet biofuel and biogasoline. In the present commercial method, deoxygenation is directly applied to vegetable oils through liquid phase hydrotreatment. This method is expensive because it consumes a large amount of hydrogen and requires severe operating conditions. The objective of this study was the production of a diesel-like hydrocarbon fuel that can be considered as drop-in replacement for petroleum-based diesel fuels, by catalytic thermal decarboxylation of Mg-Zn basic soap. In particular, this study investigated the decarboxylation of Mg-Zn basic soap at low temperature and pressure, without external supply of hydrogen. The Mg-Zn basic soap (9/1 mole ratio of Mg/Zn) was derived from palm stearin and decarboxylated at 350 Â°C and atmospheric pressure for 5 hours. The basic soap effectively decarboxylated, yielding a diesel-like hydrocarbon fuel with a liquid product yield of 62%-weight. The resulting hydrocarbon product is a complex mixture consisting of normal paraffins in the range of carbon chain length C8âC19, iso-paraffins and various olefin products.